(untitled) (UNIZIK Journal of Marketing, 2024)
Studies on modern shopping centers tilted toward super-regional and regional shopping centers and their findings are mostly contextual in nature, reflecting Western World and regional pattern of the patronage, despite the relevance of neighborhood shopping centers in the retail business landscape. The study analyzed spatial pattern of patronage of neighborhood shopping centers in Gusau Town, Nigeria. Five neighborhood shopping centers were sampled purposively from six political wards, and a total of 400 utility and recreational shoppers were sampled through convenience sampling technique. Data was collected using interview schedule and GPS device. Spatial variation in patronage of neighborhood shopping centers’ was analyzed using spatial analysis toolbox of ArcGIS 10.0V software. Descriptive statistics was used in determining patronage pattern and to analyzed demographic characteristics of shoppers. It was discovered that patronage of Shopping Centers varies spatially, and majority of the customers comes from Tudun Wada and Sabon Gari wards. It was also found that patronage of modern Shopping Centers at local level is the same with what is obtainable at regional and global levels, where the patronage is dominated by middle- and high-income earners which have significant level of literacy/western education who are driven by convenience, safety, quality of goods and leisure aspect of shopping. It is concluded that spatial variation in the patronage is a product of physical divide between the high- and middle-income customers at one side and low-income customer at the other side. The retail managers have a duty to ensure that their shopping centers have large trade area which covers at least two-third of the population of their operational base (location) for the sustainability and prospect of their business. It was recommended that more investment should be made in Neighborhood Shopping Center development because of its potentials in job creation and commercial viability